2013
DOI: 10.9755/ejfa.v25i7.15989
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic triterpenoids with antimicrobial activity from the leaves of<br>Vernonanthura patens (Asteraceae)

Abstract: Vernonanthura patens (Kunth) H. Rob, is native to Mexico and South America and found in dry or wet forests or pine forests. They are reaching in height from 0 to 1865 meters above sea level (masl). They are distributed throughout South America, in Central America: Mexico, Belize, Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua, Panama, and northern South America: Venezuela, western South America: Bolivia, Colombia, Ecuador and Peru. Three pentacyclic triterpenoids from the leaves were isolated by chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
1
2
2
1
Order By: Relevance
“…However, most of the previous studies showed antibacterial activity of this compound against Bacillus subtilis , Staphylococcus aureus and Escherichia coli 29 , 30 . In contrast to the present study, Manzano et al 31 reported no antifungal activity of 2 against Penicillium chrysogenum and Fusarium oxysporum , showing specificity of this compound against M. phaseolina. Betulin ( 3 ) has been reported fungicidal against a number of fungi including Fusarium solani and Aspergillus niger and its effect was equal to standard antifungal drug miconazole 32 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, most of the previous studies showed antibacterial activity of this compound against Bacillus subtilis , Staphylococcus aureus and Escherichia coli 29 , 30 . In contrast to the present study, Manzano et al 31 reported no antifungal activity of 2 against Penicillium chrysogenum and Fusarium oxysporum , showing specificity of this compound against M. phaseolina. Betulin ( 3 ) has been reported fungicidal against a number of fungi including Fusarium solani and Aspergillus niger and its effect was equal to standard antifungal drug miconazole 32 .…”
Section: Discussioncontrasting
confidence: 99%
“…Lupeol ( 1 ), a pentacyclic triterpenoid, has also been isolated from a number of plant species including green pepper, mangoes, strawberry, grapes, white cabbage and olive, and is known to have useful effect as a preventive and therapeutic agent against a number of ailments 39 . Although in the present study, it found comparatively less effective against M. phaseolina, however, it was highly effective against Penicillium notatum causing 90% growth inhibition when used in 200 µg mL −1 concentration 31 . It was also inhibitory to the growth of Fusarium solani, Aspergillus niger, Rhizoctoia phaseoli, Candida albicans, Penicillium chrysogenum, Cantharellus flavus and Microsporum canis, and its antifungal activity was comparable with miconazole 40 .…”
Section: Discussioncontrasting
confidence: 65%
“…Unfortunately there is no study on the volatiles of V. patens reported in the literature for comparison. These results confirm the wealth in terpene compounds of V. patens from the Ecuadorian coast, for which Manzano et al, [13] [14] identified pentacyclic triterpenoids as major constituents of the species. The results are reported for first time in the species growing in Ecuador.…”
Section: Resultssupporting
confidence: 87%
“…31 It also showed antifungal activity against Fusarium oxysporum and Penicillium notatum. 32 Triterpene 1c significantly reduced the 451Lu tumor growth in athymic nude mice, 33 inhibited the proliferation of MDA-MB-231 human breast cancer cells in a dose dependent manner 34 and induced growth inhibition and apoptosis in hepatocellular carcinoma SMMC7721 cells by down-regulation of the death receptor 3 (DR3) expression. 35 It exhibited potent anti-inflammatory activity in an allergic airway inflammation model by a significant reduction in eosinophils infiltration and in Th2-associated cytokines levels that trigger the immune responses in asthma.…”
Section: Resultsmentioning
confidence: 99%